Scientific Opinion on the safety and efficacy of vitamin B1 (thiamine mononitrate and thiamine hydrochloride) as a feed additive for all animal species based on a dossier submitted by DSM Nutritional Products - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (Wiley, 2011)
Abstract Thiamine mononitrate administered via feed and thiamine hydrochloride via water for drinking are safe for the target animals having a wide margin of safety. The use of thiamine mononitrate and thiamine hydrochloride as additives in animal nutrition is safe for consumers. Since no data on inhalation toxicity of thiamine mononitrate and thiamine hydrochloride has been provided, inhalation of dust is considered as potentially hazardous. Diluted solutions of thiamine mononitrate were not irritant to skin and eyes, the pure substances have not been tested. Thiamine mononitrate and thiamine hydrochloride are regarded as skin and eye irritants. On the basis of published literature, thiamine should be considered as a sensitiser. A risk for the environment resulting from the use of thiamine mononitrate and thiamine hydrochloride in animal nutrition is not foreseen. Thiamine mononitrate and thiamine hydrochloride are regarded as effective sources of vitamin B1.